Influence of Ambient Sound Fluctuations on the Crossing Decisions of Pedestrians who Are Visually Impaired: Implications for Setting a Minimum Sound Level for Quiet Vehicles. (September 2014) - Kim, Dae Shik; Emerson, Robert Wall; Naghshineh, Koorosh; Myers, Kyle
Introduction: Following the passage of the Pedestrian Safety Enhancement Act in the United States, the National Highway Traffic Safety Administration is setting a minimum sound level for hybrid and battery electric vehicles. With an aim to aid this effort, the present study investigated the timing and performance of critical street-crossing decisions by pedestrians who are visually impaired (that is, those who are blind or have low vision) at selected intersections. Methods: Fourteen visually impaired adults with typical hearing along with a sighted experimenter made street-crossing decisions by indicating when they would initiate crossing using radio controller handsets. Participants' decisions were compared with the sighted experimenter's decisions to determine the level of their risk. Results: At the residential intersection, the percentage of risky crossing decisions by participants was significantly lower when the decisions were made at lower ambient sound levels (M = 8.9%, SD = 6.9%) than when they were made at higher ambient sound levels (M = 35.3%, SD = 21.2%), p < .001. The participants were able to make significantly fewer risky crossing decisions during the windows of time when the ambient sound level was lower at the major-and-minor-street intersection as well ( p = .001). Discussion: Participants were often able to take advantage of the troughs in ambient sound for making street-crossing decisions, and the decisions made in lower ambient sound level conditions were generally less risky than those made in higher ambient sound level conditions. Implications for practitioners: Given the finding that the level of ambient sound detected when participants made crossing decisions was much lower than the average ambient sound level at a given intersection, as long as there are noticeable dips in ambient sound, average ambient sound level at a given intersection may not be the most relevant measure of background sound level when determining a minimum sound level for the hybrid and electric vehicles.